2016
DOI: 10.1186/s12879-016-1655-3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of extended-spectrum ß-lactamase producing enterobacteriaceae among clinical isolates in Burkina Faso

Abstract: BackgroundNothing is known about the epidemiology and resistance mechanisms of extended-spectrum ß-lactamase-producing Enterobacteriaceae (ESBL-PE) in Burkina Faso. The objective of this study was to determine ESBL-PE prevalence and to characterize ESBL genes in Burkina Faso.MethodsDuring 2 months (June-July 2014), 1602 clinical samples were sent for bacteriologic investigations to the microbiology laboratories of the tree main hospitals of Burkina Faso. Isolates were identified by mass spectrometry using a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
63
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(129 citation statements)
references
References 44 publications
44
63
13
1
Order By: Relevance
“…One hundred and eighty-seven (38.5%) of the 486 isolates obtained were ESBL producing with 21.0% from male. This is in line with the reports of Siraj et al (2014) in Ethiopia and Ouedraogo et al (2016) in Burkina Faso in which urine yielded a higher number of bacterial isolates. Hijazi et al (2016) also reported a similar finding in Lebanon with male children having a higher colonization frequency (33.9%) of ESBL-E in contrast to their female counterparts that had a frequency of (15.9%).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…One hundred and eighty-seven (38.5%) of the 486 isolates obtained were ESBL producing with 21.0% from male. This is in line with the reports of Siraj et al (2014) in Ethiopia and Ouedraogo et al (2016) in Burkina Faso in which urine yielded a higher number of bacterial isolates. Hijazi et al (2016) also reported a similar finding in Lebanon with male children having a higher colonization frequency (33.9%) of ESBL-E in contrast to their female counterparts that had a frequency of (15.9%).…”
Section: Discussionsupporting
confidence: 82%
“…Mathlouthi et al (2016) affirm this finding in their report of isolates from Tunisian and Libyan hospitals with 80% resistance to ceftazidime, cefotaxime, amoxicillin + clavulanic acid, amoxicillin and ciprofloxacin. Our report of 38.5% prevalence of ESBL-E in this study is relatively high; however a similar study by Ouedraogo et al (2016) in Burkina Faso recorded a higher prevalence of 58%. This variation in findings could be explained by the size, duration and area where the two studies were conducted.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The results from our study however, reflect the global trend toward a pandemic spread of CTX-M-type ESBLs in various Enterobacteriaceae. These findings agree with other contemporary studies from around the world that show that ESBL genes of the CTX-M are dominant in Tanzania, Burkina Faso, Texas, Spain, Brazil, Latin America, [32][33][34][35][36][37]. In similarity to our findings, Ahmed et al [38] reported that blaTEM was the most frequent β-lactamase-encoding gene in Egypt.…”
Section: Discussionsupporting
confidence: 93%
“…The major ESBL E. coli producer (18.2%) was isolated from urine samples (Raut et al, 2015). Ouedraogo et al (2016) found that blood cultures had the highest proportion of ESBL isolates. In previous study, the distribution of ESBL producers was most prevalent in blood (22.2%) and urine samples (17.6%).…”
Section: Discussionmentioning
confidence: 99%